Biolistic Transformation of Selected Orchid Hybrids for Improved Shelf Life and Cloning of Partical ACC Oxidase Gene from Oncidium Gower Ramsey - Mohana Anita (2005)
The aim of the project was to lengthen the shelf life of orchid flowers to get superior quality flowers. The strategy used was by retarding the internal ethylene biosynthesis pathway through transferring the ACC oxidase gene in the reverse orientation (antisense) into the orchid cells of Dendrobium Savin White and Oncidium Gower Ramsey. This is complimented by isolation of ACC oxidase gene fragments from Oncidium for future genetic manipulation. A tissue culture system was established to provide plant materials for transformation work. Protocorm-like bodies (plbs) of Dendrobium and Oncidium were used to induce callus on half strength MS (Murashige and Skoog, 1962) medium. In Dendrobium, unwounded plbs or wounded plbs were tested to induce callus with Picloram (0, 0.6, 0.7, 0.8, 0.9 mg/L) in combination with Kinetin (0, 0.6, 0.7, 0.8, 0.9 mg/L). Oncidium callus was induced with Picloram (0, 12, 20, 30, 40, 50 mg/L) or 2,4 Diphenoxyacetic acid (2,4-D) at concentrations of 0, 5, 10, 15, 20, 25 mg/L separately. The highest rate of Dendrobiurn callus (42%) was obtained using unwounded plbs with 0.9 mg/L Picloram combined with 0.8 mg/L Kinetin. Unwounded Dendrobium plbs produced the highest rate of callus (17%) with combinations of 0.8 mg/L Picloram and 0.7 mg/L Kinetin or 0.9 mg/L Picloram and 0.9 mg/L Kinetin. The most effective callus induction (43.3%) for Oncidium was obtained with 5mg/L of 2,4-D. Picloram at 50 mg/L had the highest rate of callus induction (36.7%). Histological observations revealed that callus cells were undifferentiated whereas plbs had distinctive meristematic areas. Regeneration of Dendrobium and Oncidium callus was successfully obtained. Before transformation, a protocol was established for the selection of putative transgenic cells using hygromycin. Optimization of particle bombardment parameters (helium gas pressure and target/macrocarrier distance) was done with GUS assay. Helium pressure of 1100 psi (7580 kPa) with platform levels 1,3 or 1,4 was found suitable. ACC oxidase antisense construct (pPhACOAS1) was used for transformation and after hygromycin selection; one transgenic line of Dendrobium was obtained and regenerated. Confirmation of the transformed "lines" was done by Polymerase Chain Reaction (PCR) and Southern Blot. wwwks.Jm- W Y 8 A ACC oxidase gene was isolated from pollinated Oncidium flowers. Physical changes during senescence of pollinated flowers were observed and ribonucleic acid (RNA) was isolated from various stages after pollination (0 hr, 18 hrs, 24 hrs, 36 hrs, 48 hrs, 72 hrs) and unpollinated flowers. ACC oxidase expression from the RNA samples was analyzed through Northern Blot and showed increased levels of expression over time. The Reverse- Transcription Polymerase Chain Reaction (RT-PCR) technique was used to isolate ACC oxidase gene fragments from the RNA samples and was successfully amplified from three stages (unpollinated, 18 hours and 48 hours after pollination). The gene fragments were then cloned into vectors, sequenced and characterized. The nucleic sequence and deduced amino acid sequence obtained from the three different stages had high homology with other ACC oxidase sequences in the Genebank. The analysis of the positive clones obtained showed two versions of ACC oxidase sequences (OncACO1 and OncAC02) which were successfully isolated.